Czynnik gospodarczy jako predyktor zachowań wyborczych - Turska-Kawa, Agnieszka (Political Preferences, 2015)
Economic factor as a predictor of voting behaviour The article seeks to answer the question of whether, and if yes - to what extent, voters are guided by economic issues in their decisions about electoral participation (activity or passivity in the elections). The analysis of this question was carried out in the context of declared electoral behavior of the respon- dents in elections which took place in 2014, namely to the European Parliament and the Polish regional (voivodship) parliaments. Detailed analysis was aimed at verifying the sociodemographic variables that could significantly differentiate the subjective importance of the economic factor in decisions taken on electoral participation. These empirical considerations took into account variables such as sex, age, education, marital status, financial situation, professional status and place of residence. Key words: electoral behavior, economic issues, electoral participation